Analisis Keberhasilan Program Zakat dalam Meningkatkan Kesejahteraan Mustahik di Kabupaten Langkat - Azkia Risyda, Putri; Ikhsan Harahap, Muhammad; Nasution, Juliana (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the success of the zakat program in improving the welfare of those who mustahik (receiver) in Langkat Regency. The study used a qualitative approach with triangulation methods through in-depth interviews, observations, and documentation studies with zakat administrators, local government officials, mustahik, and muzakki (receiver). The results indicate that zakat management by the Langkat Regency BAZNAS (National Agency for the Protection of the Poor) has had a multidimensional impact on mustahik, including improving housing quality, strengthening access to education, increasing income through economic empowerment programs, and increasing community religious awareness. The synergy between BAZNAS and the local government has also strengthened the effectiveness of zakat collection and distribution. Although challenges remain in optimizing funds and empowering business mentoring, the zakat program in Langkat Regency has substantively demonstrated success as an instrument for sustainable socio-economic empowerment and contributing to reducing regional poverty.